Modulation of Gut Microbiota and Immune System by Probiotics, Pre-biotics, and Post-biotics - Liu, Yue; Wang, Jiaqi; Wu, Changxin (Frontiers in Nutrition, 2022)
The human gastrointestinal tract harbours a complex microbial community, which interacts with mucosal immune system closely. Gut microbiota plays a significant role in maintaining host health, which could supply various nutrients, regulate energy balance, modulate immune response and defence against pathogens. Therefore, maintaining favourable equilibrium of gut microbiota through modulating bacteria composition, diversity and their activity is beneficial to host health. Several studies have shown that probiotics and prebiotics could directly and indirectly regulate microbiota and immune response. In addition, postbiotics including the bioactive metabolites produced by gut microbiota, and/or cell-wall components released by probiotics, also have been shown to inhibit pathogen growth, maintain microbiota balance and regulate immune response. This review summarises the studies concerning the impact of probiotics, prebiotics, and postbiotics on gut microbiota and immune systems, and also describes the underlying mechanisms of beneficial effects of these substances. Finally, the future and challenges of probiotics, prebiotics and postbiotics are proposed.